Sünde in der heiligen chrisdichen Kirche Ekklesiologische und seelsorgerliche Überlegungen - Mayer, Rainer (Theologische Beiträge, 2022)
If one concentrates the holiness of the church ontologically on the empirically tangible form of the institution church, as is done in the Roman Catholic tradition, one must hold on to the holiness of the church also in the external-institutional sense. But when blatant sin occurs in the church, this concept of church enters a state of crisis. The tendency arises to conceal and cover up transgressions so that the church (apparently) remains holy. The Reformation understanding of church, on the other hand, does not focus primarily on the institutional aspect, but on an act of God. The holiness of the church is drawn into the event of justification. As a result, the holiness of the church tends to be shifted into the realm of the invisible. Therefore, in Protestantism it is readily admitted that the church has sinned and is sinning. However, this easily leads to self-justification. This article proposes that the Protestant understanding of church must not focus solely on God's act of justification (or even on the invisible church). Instead, Bonhoeffers understanding of the church as the "Unity of Act and Being" is helpful in this regard. From this perspective not only the "Protestant culture of guilt" is overcome, but also the lax attitude "we are all sinners anyway" is dealt with.
CRIS-Team Scopus Importer:2022-09-16